The role of the special jurisdiction for peace in the Urabá region, in Colombia JEP (2018)
More than 50 years of armed conflict have framed the life of present innocent persons in the Colombian territory, it disputes for control of the territory, political interests between groups: paramilitary, the FARC-EP and Military Forces, human rights violation, forced displacement, massacres, appropriation of grounds, direct affectations to more vulnerable population, girls, children, women, ethnic groups, the region of the Urabá is a radiography of this reality. The recognition of the conflict armed on the part of the Government and the FARC-EP signs a precedent of vital importance in the history of Colombia, from 2012 that the dialogues tables establish in Cuba for the purpose of coming to a peace agreement. On November 11, 2016 the Final Agreement is signed with all the rules and guarantees of the peace, which center is “the victim” and an environment to her fix the special treatments of social conciliation with the target to compensate the pain, to repair the victims, to generate guarantees for those who decide to sign the agreement and contribute with the revelation of the absolute truth, of repair to the victims. Product of the agreement six important topics talk each other: Integral Rural reform, Political participation, Cease-fire and hostilidades bilateral and definitive and the surrender of the weapon, Solution to the problem of the illicit drugs, mechanisms of implementation and cross-check; half-close to the Agreement and its implementation details the function of the Special Jurisdiction for the Peace like entity of justice and the intervention of the room of Recognition Truth and Responsibility in the Region of the Urabá and the concepts born in mind to give him priority.